Promotion of urban public transport - European Conference of Ministers of Transport ([Brussels], 1973)
The aim of the study is to put on paper the various measures taken to attract more custom to transport services and secondly to assess the main results achieved
osc 31/01/2019
Loans
Keywords: Local transit; Urban transportation; Europe